(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
In this article, utilizing game technologies, including computer-based ones, has become a staple in English language teaching, offering significant benefits such as fostering intercultural communicative competencies, boosting motivation, and enhancing self-organization. This study aims to provide an objective overview of how educators incorporate game-based methods and gamification techniques in both traditional classroom settings and remote learning environments. The theoretical significance of this research lies in the examination of empirical studies conducted by domestic and international scholars on English language teaching, which informed the development of a questionnaire used to gather insights from English teachers. The questionnaire sought to capture teachers’ experiences with implementing gamification techniques and game technologies in both in-person and online English lessons. The study sample comprised 48 English teachers with varying levels of teaching experience (ranging from 1 to 13 years) and students aged between 3 and 60 years old. Through the questionnaire, teachers provided insights into their use of gamification techniques and game technologies, shedding light on their practical application in language learning contexts.